Stakeholders’ perspective of corporate social and environmental responsibility (CSER) practices and reporting in an emerging economy - Hossain, Md. Moazzem; Rowe, Anna; Quaddus, Mohammed (Unknown, 2013)
The purpose of this paper is to explore the views of key stakeholders on corporate social and environmental responsibility (CSER) practices and reporting in Bangladesh. The paper addresses a salient gap in the CSER literature evidenced by the dearth of studies that explore the views of non-managerial and economically less powerful stakeholders from an emerging economy such as Bangladesh. This study applied qualitative research method and utilised philosophical notions such as constructivist ontology and interpretive epistemology. A series of in-depth semi-structured interviews conducted with 14 key stakeholder groups, complemented by utilizing observations with pragmatic local working knowledge from one of the researchers. By using the predominant system-oriented theories such as legitimacy theory, stakeholder theory and institutional theory, this research found that stakeholders expect more institutional involvement including media, NGOs, regulatory authority and civil societies’ support to ensure more CSER practices and reporting by Bangladeshi companies. The findings also report that stakeholders are not satisfied with the current CSER practices and reporting due to organisations’ focus on marketing and profit making objectives. This study suggests that local standard setting bodies along with institutional involvement can play a significant role in fulfilling stakeholders’ expectations towards CSER reporting in Bangladesh.